ANALYSIS OF ADDED VALUE OF BADA RACKET AGROINDUSTRY IN MATANG KRUET VILLAGE, PANTE BIDARI DISTRICT, KABUPATEN EAST ACEH (Case Study: UD.CITA RASA) - Quswarnika Quswarnika; Suryadi Suryadi; Irada Sinta (Jurnal Mahasiswa Agribisnis, 2024)
Banana is a fruit plant, a source of vitamins, minerals and carbohydrates. In Indonesia, bananas that are planted either on a household or garden scale are less intensively maintained. Thus, Indonesian banana production is low, and unable to compete in the international market. In Southeast Asia, Indonesia is one of the countries with the largest number of fruit varieties. This research aims to analyze the added value of the banana agroindustry, especially in the UD bada racket agroindustry. TASTE in village Matang Kruet, Pante Bidari District, East Aceh Regency. This research was carried out in Matang Kruet village, Pante Bidari District, East Aceh Regency, namely at the UD racket business. CITA RASA, the determination of the location for this research was carried out deliberately (purposive sampling), with the consideration that the UD racket business. CITA RASA is a more advanced business compared to other bada racket businesses by producing bada rackets in one production producing 300 packs. The types of data in this research include quantitative data and qualitative data using the Hayami method. Based on the results of research that has been carried out, the income from bada racket production is IDR. 507,340/production. The average output (sales volume) is 300 packs/production. The added value of the racket is IDR. 7,675 with a value added ratio of 53.30%.